Investigation into the quality of life of an employee affected by HIV/AIDS - Vollenhoven, Salome Minky (Stellenbosch : Stellenbosch University, 2008)
Thesis (MCur (Interdisciplinary Health Sciences. Nursing Science))--Stellenbosch University, 2008.